<=> (24-1)(24+1).....(2m+1)=23m-218
<=> 22m-1+1=23m-218
<=> 22m=23m-218
<=>2m=3m-218
=>m=218
<=> (24-1)(24+1).....(2m+1)+1=23m-218
<=> 22m-1+1=23m-218
<=> 22m=23m-218
<=>2m=3m-218
=>m=218
ở dưới mình nhầm nha!!!
<=> (24-1)(24+1).....(2m+1)=23m-218
<=> 22m-1+1=23m-218
<=> 22m=23m-218
<=>2m=3m-218
=>m=218
<=> (24-1)(24+1).....(2m+1)+1=23m-218
<=> 22m-1+1=23m-218
<=> 22m=23m-218
<=>2m=3m-218
=>m=218
ở dưới mình nhầm nha!!!
Thu gọn M= \(\left(2^1+1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
Giúp mình gấp với nhé!
Tìm \(x\)
a) \(\left(8-5x\right)\left(x+2\right)+4\left(x-2\right)\left(x+1\right)+2\left(x-2\right)\left(x+2\right)=0\)
b) \(\left(8x-3\right)\left(3x+2\right)-\left(4x+7\right)\left(x+4\right)=\left(2x+1\right)\left(5x-1\right)-33\)
Tính M = \(\left(1-\dfrac{1}{2^2}\right)\left(1-\dfrac{1}{3^2}\right)\left(1-\dfrac{1}{4^2}\right)...\left(1-\dfrac{1}{2017^2}\right)\)
Tìm x, biết:
a) \(\left(2x+3\right)\left(x-4\right)+\left(x-5\right)\left(x-2\right)=\left(3x-5\right)\left(x-4\right)\)
b) \(\left(8x-3\right)\left(3x+2\right)-\left(4x+7\right)\left(x+4\right)=\left(2x+1\right)\left(5x-1\right)\)
c) \(\left(3x-5\right)\left(7-5x\right)-\left(5x+2\right)\left(2-3x\right)=4\)
Tìm x :
a, \(2\cdot\left(5x+1\right)-7\cdot\left(3x-2\right)=4\cdot\left(2x-1\right)+3\cdot\left(2-x\right)\)
b, \(-4\cdot\left(\dfrac{1}{2}x-3\right)+\dfrac{7}{2}\cdot\left(2x-1\right)+x=5x\cdot\left(1-x\right)\)
Tính rồi so A và B :
\(A=\left(0,25\right)^{-1}.\left(1\dfrac{1}{4}\right)^2+25\left[\left(\dfrac{4}{3}\right)^{-2}:\left(1,25\right)^3\right]:\left(\dfrac{-2}{3}\right)^{-3}\)
\(B=\left(0,2\right)^{-3}.\left[\left(\dfrac{-1}{5}\right)^{-2}\right]^{-1}+\left[\left(\dfrac{1}{2}\right)^{-3}\right]^{-2}:\left(\dfrac{1}{8}\right)^{-1}-\left(2^{-3}\right)^{-2}:\dfrac{1}{2^6}\)
tìm x
\(\left[\left(x+1\right)\left(2-x\right)-\left(x^2-1\right)\right]:\left(x+1\right)=2\)
Tìm x biết :
a) \(\left(x-2\right)^3+6\left(x+1\right)^2-x^3+12=0\)
b) \(\left(x-5\right)\left(x+5\right)-\left(x+3\right)^3+3\left(x-2\right)^2=\left(x+1\right)^2-\left(x+4\right)\left(x-4\right)+3x^2\)
c) \(\left(2x+3\right)^2+\left(x-1\right)\left(x+1\right)=5\left(x+2\right)^2-\left(x-5\right)\left(x+1\right)+\left(x+4\right)^2\)
d) \(\left(1-3x\right)^2-\left(x-2\right)\left(9x+1\right)=\left(3x-4\right)\left(3x+4\right)-9\left(x+3\right)^2\)
1. \(\frac{1}{2}x^2-\left(\frac{1}{2}x-4\right)\frac{1}{2}x=-14\)
2. \(3\left(1-4x\right)\left(x-1\right)+4\left(3x-2\right)\left(x+3\right)=-27\)
3. \(6x\left(5x+3\right)+3x\left(1-10x\right)=7\)
4. \(\left(3x-3\right)\left(5-21x\right)+\left(7x+4\right)\left(9x-5\right)=44\)
5. \(\left(-2+x^3\right)\left(-2+x^2\right)\left(-2+x^2\right)=1\)